العوامل المؤثرة على تعامل المستهلكين مع أ نشطة التجارة الالكترونية ( دراسة ميدانية ) - عثمان يوسف, ردينة (Recherches économiques et managériales; Vol. 14 (2013): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (DÉCEMBRE))
تركز هذة الدراسة على العوامل المؤثرة على تعامل المستهلكين مع انشطة التجارة الالكترونية بهدف التعرف على مدى ادراك المستهلكين لانشطة التجارة الالكترونية وسماتها وما هي عوامل الجذب للتعامل مع هذة الانشطة ومخاوف المستهلكين من التعامل معها ولقد قسمت هذة الدراسة الى اربع محاور وكل محور يتعلق بفرضية من فرضيات الدراسة و يضم مجموعة من الاسئلة التي من خلالها يتم اختبار فرضيات الدراسة وصول الى هدف هذة الدراسة ومن اجل جمع البيانات لهذة الدراسة لقد تم تصميم استمارة تحتوي على (26 ) سؤال موزعة على محاور وفرضيات الدراسة ولقد وزعت الاستبانة في مدينة عمان والزرقاء ولقد تم الحصول على (255 )استمارة صالحة للتحليل الاحصائي .ومن خلال معالجة البيانات احصائيا كانت نتائج التحليل هي رفض فرضيات العدم الاربعة وقبول الفرضيات البديلة وهذا يشير الى ان افراد العينة يدركون انشطة التجارة الالكترونية وسماتها ويجدون بان هنالك عوامل جذب للتعامل مع هذة الانشطة ولكن لديهم عدد من المخاوف في التعامل مع هذة الانشطة . Abstract This study focuses on the factors affecting consumers' deal with electronic commerce activities in order to identify the extent of consumer awareness of e-commerce activities and characteristics and what are the attractions factors to deal with these activities and consumer fears of dealing with it. This study was based on four dimensions and each one is related to one of the study hypotheses and includes a set of questions through which the study hypotheses are tested to reach the goal of this study . for collecting data , a questioner has been designed which contain (26) Question distributed on study axes and hypotheses and has distributed in Amman and AL-Zarqaa cities and (255) obtained form were suitable for statistical analysis. through statistical processing of the data the results is the rejection of all four null hypotheses and acceptance of the alternative ones, that indicates the sample were aware of e- commerce activities and features and find that there are attraction to deal with these activities but they have a number of concerns in dealing with these activities.